A MULTI SLICE COMPUTED TOMOGRAPHY CORONARY ANGIOGRAPHIC STUDY OF CORONARY ARTERY DISEASE IN SOLDIERS WITH CHEST PAIN - Shahzad, Syed Khurram; Siddiqui, Abdul Hameed; Samore, Naseer Ahmad (Pakistan Armed Forces Medical Journal, 2014)
Objective: The study is sought to highlight the role and results of MSCT angiography in scenario of acute chest pain to determine or exclude significant coronary artery disease in patients who do not have high risk features for significant coronary disease. Study Design: Descriptive study. Place and Duration: Computed topography department, Armed Forces Institute of Cardiology, National Institute of Heart Diseases Rawalpindi from September 2013 to December 2013. Patients and Methods: A total of 150 patients (soldiers) who were referred to this hospital with chest pain and who did not have high risk features were evaluated by multi slice computed coronary angiography. Results: One hundred and fifty patients who reported to this hospital with chest pain were evaluated by multi slice computed tomography (MSCT) angiography. Their age ranged from 20 to 53 years. Cases studied were those having low probability of coronary artery disease. Patients having high probability of coronary disease, acute coronary syndrome or definite coronary artery disease were excluded from this study and were evaluated by conventional coronary angiography, 114 (76%) patients showed normal coronary arteries. 6 (4%) had subcritical coronary disease, 5 (3.33%) had only minor irregularity in coronary arteries, 4 (2.66%) had significant coronary artery disease that necessitated coronary angiogram. 16 (10.66%) cases had muscle bridge in left anterior descending artery. One (0.66%) patient had patent graft after coronary artery bypass graft surgery. Three (2%) patient’s had patent stents in coronary arteries. While 1(0.66%) patient had aberrant origin of coronary artery. There were no side effects observed during study. Conclusion: Patients presenting with chest pain with low risk features can be studied conveniently with MSCT angiography. Prevalence of significant coronary artery disease is low. MSCT angiography is a very useful, convenient and safe tool to screen low risk patients to rule out presence of significant coronary artery disease. Keywords: